A pyrazine bis-adduct of a binuclear rhodium(II) carboxylate containing 3,4,5-triethoxybenzoate as the equatorial ligand - Castro, M.A. (2002)
The title compound, tetrakis(μ-3,4,5-triethoxybenzoato κ 2 O:O′)bis[(pyrazine-κN)rhodium(II)](Rh-Rh). [Rh 2 (C 13 -H 17 O 5 ) 4 (C 4 H 4 N 2 ) 2 ], crystallizes on an inversion centre in the triclinic space group P1̄. The equatorial carboxylate ligands bridge the two Rh 11 atoms, giving a binuclear lantern-like structure. The pyrazine molecules occupy the two axial coordination sites. The phenyl rings are titled by ca 10° with respect to the attached carboxylate groups. The pyrazine planes have a torsion angle of ca 19° around the Rh-N bond with respect to the plane of the nearer carboxylate group and are not coplanar with the Rh-Rh bond.